2020
DOI: 10.1007/s42452-020-03795-8
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization and mechanical performance analysis of biaxially oriented PLA/PCL tubular scaffolds for intended stent application

Abstract: Polylactic acid (PLA) and its blends are potential materials for bioresorbable vascular tubular scaffold (TS) manufacturing. The usual method for TS fabrication for intended stent application includes firstly extruding the polymeric tube and then subjected to post-processing operations for tailoring its mechanical properties. In this study, PLA/PCL blend TS was fabricated by using a novel and facile fabrication method, which eliminates the much-needed post-processing operation on the extruded TS. Two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Shifting of the bands indicated that there is non‐covalent interaction between TA, TBC, and alginate 33 . Interpenetrating polymer fibers can exert blend characteristics during in vivo and in vitro studies 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifting of the bands indicated that there is non‐covalent interaction between TA, TBC, and alginate 33 . Interpenetrating polymer fibers can exert blend characteristics during in vivo and in vitro studies 34 …”
Section: Resultsmentioning
confidence: 99%
“…33 Interpenetrating polymer fibers can exert blend characteristics during in vivo and in vitro studies. 34 F I G U R E 1 Scanning electron microscopy (SEM) and macroscopic photographs of Alg-nHA (A, B), Alg-TA-nHA (C, D) and Alg-TBC-nHA (E, F) scaffolds.…”
Section: Chemical Characterization Of Scaffoldsmentioning
confidence: 99%
“…These BAE tubes were stored at −20°C, which was further used for fabricating cardiovascular stents. Detailed comparison studies on both the BAE tube materials already been performed for cardiovascular stent application 22,24,25 …”
Section: Methodsmentioning
confidence: 99%
“…Detailed comparison studies on both the BAE tube materials already been performed for cardiovascular stent application. 22,24,25…”
Section: Tube Extrusionmentioning
confidence: 99%
“…[23][24][25] Blending the PLA and PCL provides an amalgamation of these preferred properties, provoking their blend to be suitable for diverse applications such as packaging, tissue engineering, and cardiovascular applications. [26][27][28][29] Also, investigating the performance of PLA/PCL blend in the presence of various nanoparticles and its influence on the microstructure as the third component has been recently in the center of attention of researchers. [30][31][32] For example, Zhu et al [33] studied montmorillonite (MMT) nanoparticles role on the interfacial interactions in the PCL/PLA blend.…”
Section: Introductionmentioning
confidence: 99%